Pengaruh Biaya Audit, Sistem Akuntansi Klien, Dan Tekanan Anggaran Waktu Terhadap Kualitas Audit - Jonathan Nainggolan (Universitas Advent Surya Nusantara, 2025)
This study examines the influence of audit fees, client accounting systems, and time budget pressure on audit quality. Data were collected through a survey involving 59 auditors working at public accounting firms in Jakarta. The findings revealed that client accounting systems and time budget pressure significantly affect audit quality, while audit fees have no significant impact. A robust client accounting system enhances the effectiveness of audit procedures, providing auditors with accurate and reliable financial data. Conversely, time budget pressure can either improve audit quality through efficiency or compromise it by neglecting important steps, depending on the auditor's experience and time management skills. Surprisingly, the study found a positive effect of time budget pressure on audit quality, suggesting the role of enhanced focus and resource allocation under strict deadlines. These results contribute to a deeper understanding of the dynamic interactions between external factors and internal auditor competencies, emphasizing the need for effective training and professional development in the audit field.